PET/CT imaging detects intestinal inflammation in a mouse model of doxorubicin-induced mucositis - Dalby, Sina; Skallerup, Sofie; Baun, Christina; Christensen, Lene Gaarsmand; Rathe, Mathias; Palner, Mikael; Husby, Steffen; Moeller, Jesper Bonnet (Frontiers in Oncology, 2022)
Introduction A severe side effect of cancer chemotherapy is the development of gastrointestinal mucositis, characterised by mucosal inflammation. We investigated if 2-deoxy-2-[18F] fluoro-D-glucose positron emission tomography combined with computed tomography (2-[18F]FDG-PET/CT) could visualise gastrointestinal mucositis in mice treated with the chemotherapeutic agent doxorubicin. Methods In this study, gastrointestinal inflammation was longitudinally evaluated by 2-[18F]FDG-PET/CT scans before and 1, 3, 6, and 10 days after treatment with doxorubicin. Doxorubicin-treated mice were compared to saline-treated littermates using the abdominal standard uptake value of 2-[18F]FDG corrected for body weight (SUVBW). Results Abdominal SUVBW was significantly increased on day 1 (p < 0.0001), day 3 (p < 0.0001), and day 6 (p < 0.05) in the doxorubicin-treated group compared to controls. Abdominal SUVBW returned to baseline levels on day 10. In the doxorubicin group, the largest weight loss was observed on day 3 (control vs doxorubicin, mean percent of baseline weight: (98.5 ± 3.2% vs 87.9 ± 4.6%, p < 0.0001). Moreover, in the doxorubicin-treated group, villus lengths were decreased by 23-28% on days 1 and 3 in the small intestine (p < 0.05), and jejunal levels of tumour necrosis factor and interleukin-1β were significantly increased on day 3 (p < 0.05). Discussion Together, these findings indicate that sequential 2-[18F]FDG-PET/CT scans can objectively quantify and evaluate the development and resolution of intestinal inflammation over time in a mouse model of doxorubicin-induced mucositis.